The Impact of Using Artificial Intelligence in the Process of Islamic and Muhammadiyah Education - Sari, Indah Purnama; Syahra, Yohanni; Simanjuntak, Pastima (AR-RASYID : Jurnal Pendidikan Agama Islam, 2025)
Artificial Intelligence (AI) has become an increasingly popular topic in education. In the context of Islamic education, the use of AI can help improve the efficiency and effectiveness of the teaching and learning process, as well as increase student engagement and personalize learning. However, the impact of using AI in Islamic education still needs to be studied systematically. Therefore, this study aims to explore the impact of using AI in Islamic education through a comprehensive systematic study of the literature. In this study, we identified and analyzed several articles related to the use of AI in Islamic education from various literature sources, including academic journals and international conferences. The results of the study indicate that the use of AI in Islamic education has a positive impact on efficiency and productivity, personalization of learning, student engagement, assessment accuracy, and accessibility. However, the use of AI also has challenges, such as concerns about student data privacy and security, and the risk of replacing teachers with technology. Therefore, the use of AI in Islamic education needs to be developed with the right strategy and good management to maximize its benefits and minimize its negative risks.